Implementing excellence in your health care organization : managing, leading and collaborating - McSherry, Robert; Warr, Jerry (Maidenhead : McGraw-Hill, 2010)
This book considers practice issues in healthcare and explores the key issues and factors which influence the workings of a healthcare organization. The emphasis is on how the organization and those who work within it contribute to the excellence of the healthcare organization and the care it gives. Topics covered include: management and leadership; ethics; equity; governance; user-involvement; team working; and, interprofessional excellence. Case examples, real-life practice and reflective exercises are also included.